Peran Mediasi Skeptisme Auditor pada Pengaruh Kompleksitas Tugas dan Pengalaman Auditor terhadap Audit Judgement - Kiswati, Novalita Budi; Sudaryati, Erina (E-Jurnal Akuntansi, 2021)
This study aims to analyze the mediating role of auditor skepticism on the effect of task complexity and experience on audit judgment at KAP in Surabaya. This research is a quantitative study using a questionnaire as the research data instrument. The population of this study were auditors from Public Accountant Office Surabaya who were listed in IAPI in 2020. The sampling technique used was purposive sampling, so that the sample size was 45 active auditors in Public Accountant Office Surabaya.The data analysis technique used was path analysis and sobel test. The results showed that the complexity of the task and experience had a positive effect on audit judgment through the auditor’s skepticism. These results explain that auditors who increasingly show higher skepticism will be able to support the improvement of the quality of the audit judgment made even though the complexity of the audit task is getting heavier. On the other hand, auditors who are experienced or inexperienced in conducting audits will show better quality audit judgment when able to show more frequent skepticism. Keywords: Task Complexity; Experience, Skepticism; Audit Judgment.